Tuning electronic structure of metal-free dual-site catalyst enables exclusive singlet oxygen production and in-situ utilization - Gu, Chao-Hai; Wang, Song; Zhang, Ai-Yong; Liu, Chang; Jiang, Jun; Yu, Han-Qing (Nature communications, 2024)
Developing eco-friendly catalysts for effective water purification with minimal oxidant use is imperative. Herein, we present a metal-free and nitrogen/fluorine dual-site catalyst, enhancing the selectivity and utilization of singlet oxygen ( 1 O 2 ) for water decontamination. Advanced theoretical simulations reveal that synergistic fluorine-nitrogen interactions modulate electron distribution and polarization, creating asymmetric surface electron configurations and electron-deficient nitrogen vacancies. These properties trigger the selective generation of 1 O 2 from peroxymonosulfate (PMS) and improve the utilization of neighboring reactive oxygen species, facilitated by contaminant enrichment at the fluorine-carbon Lewis-acid adsorption sites. Utilizing these insights, we synthesize the catalyst through montmorillonite (MMT)-assisted pyrolysis (NFC/M). This method leverages the role of MMT as an in-situ layer-stacked template, enabling controlled decomposition of carbon, nitrogen, and fluorine precursors and resulting in a catalyst with enhanced structural adaptability, reactive site accessibility, and mass-transfer capacity. The NFC/M demonstrates an impressive 290.5-fold increase in phenol degradation efficiency than the single-site analogs, outperforming most of metal-based catalysts. This work not only underscores the potential of precise electronic and structural manipulations in catalyst design but also advances the development of efficient and sustainable solutions for water purification. Developing eco-friendly catalysts for effective water purification with minimal oxidant use is imperative. Here, authors present a metal-free and nitrogen/fluorine dual-site catalyst, enhancing the selectivity and utilization of singlet oxygen for sustainable water decontamination.